2020
DOI: 10.1111/cts.12769
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Diversity in Drug Transporters: Impact in African Populations

Abstract: Polymorphisms in drug transporters, like the adenosine triposphate‒binding cassette (ABC) and solute carrier (SLC) superfamilies, may contribute to the observed diversity in drug response in African patients. This review aims to provide a comprehensive summary and analysis of the frequencies and distributions in African populations of ABC and SLC variants that affect drug pharmacokinetics (PK) and pharmacodynamics (PD). Of polymorphisms evaluated in African populations, SLCO1B1 rs4149056 and SLC22A6 rs1158626 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…rs4149032 is an intronic SNP most common in the African population. 48 , 49 Gengiah et al reported high frequency in the SLCO1B1 (rs4149032) gene polymorphism and its association with low median rifampicin C2.5hr in the heterozygous and homozygous variant carriers. 32 Similarly, Chigutsa et al reported high allelic frequency of the SLCO1B1 rs4149032 polymorphism and 28% reductions in the bioavailability of rifampin for homozygous variants.…”
Section: Resultsmentioning
confidence: 99%
“…rs4149032 is an intronic SNP most common in the African population. 48 , 49 Gengiah et al reported high frequency in the SLCO1B1 (rs4149032) gene polymorphism and its association with low median rifampicin C2.5hr in the heterozygous and homozygous variant carriers. 32 Similarly, Chigutsa et al reported high allelic frequency of the SLCO1B1 rs4149032 polymorphism and 28% reductions in the bioavailability of rifampin for homozygous variants.…”
Section: Resultsmentioning
confidence: 99%
“…Together these studies could be used to adjust the standard recommended dose of ARV and TB drug for the African population that accounts for the presence of SNPs (Dandara et al, 2011;Rajman et al, 2020). The effects of SNPs on drug transporter genes have also been associated with increased plasma concentrations of TFV.…”
Section: Genetic Polymorphismsmentioning
confidence: 99%
“…Pharmacogenetic studies conducted with African populations have also shown high genetic diversity, which subsequently leads to varied drug transporter function and expression levels; impacting drug pharmacokinetics differently as reviewed by Rajman et al (2020) . The presence of the SLCO1B1 SNP 463C/A rs11045819 encoding the OATP1B1 protein was shown to impact rifampin pharmacokinetics differently in African populations ( Weiner et al, 2010 ; Dompreh et al, 2018 ).…”
Section: Biological Factors Modulating Drug Transporter Expression An...mentioning
confidence: 99%
“…In humans, several factors account for inter- and intra-individual differences in oral bioavailability. These include, but are not restricted to: GI surgery or chronic inflammatory intestinal conditions [ 36 ], co-administration of drugs [ 37 ], food–drug interactions, feeding condition, age and sex [ 38 ] of the patient, ethnic background [ 39 ] and the patient’s unique physiology (including phenotypic polymorphisms) [ 40 ] ( Figure 1 ). In particular, polymorphisms in transporter genes affecting expression or activity can influence bioavailability of drugs and toxins and may also predispose to certain diseases [ 2 ].…”
Section: Bioavailability and The Intestinal Epitheliummentioning
confidence: 99%